Structural and Evolutionary Insights Into the Binding of Host Receptors by the Rabies Virus Glycoprotein - Khalifa, Manar E.; Unterholzner, Leonie; Munir, Muhammad (Frontiers in Cellular and Infection Microbiology, 2021)
Rabies represents a typical model for spill-over of zoonotic viral diseases among multiple hosts. Understanding the success of rabies virus (RV) in switching hosts requires the analysis of viral evolution and host interactions. In this study, we have investigated the structural and sequence analysis of host receptors among different RV susceptible host species. Our extensive bioinformatic analysis revealed the absence of the integrin plexin domain in the integrin β1 (ITGB1) receptor of the black fruit bats in the current annotation of the genome. Interestingly, the nicotinic acetyl choline receptor (nAChR) interaction site with the glycoprotein (G) of RV was conserved among different species. To study the interaction dynamics between RV G protein and the RV receptors, we constructed and analyzed structures of RV receptors and G proteins using homology modelling. The molecular docking of protein-protein interaction between RV G protein and different host receptors highlighted the variability of interacting residues between RV receptors of different species. These in silico structural analysis and interaction mapping of viral protein and host receptors establish the foundation to understand complex entry mechanisms of RV entry, may facilitate the understanding of receptor mediated spill-over events in RV infections and guide the development of novel vaccines to contain the infection.